Antioxidant and Antihypertensive Activity Egg White Powder Produced by Pan Drying at Different Temperature and Drying Time - . Nahariah; A. M. Legowo; E. Abustam; A. Hintono (Jurnal Ilmu dan Teknologi Peternakan, 2015)
Antioxidant and antihypertensive (ACE-Inhibitors) are commonly known as bioactive molecules in foodstuff. Both molecules can be obtained naturally or through processing and preservation of egg white of poultry eggs. One way of preserving the egg white with drying method is by pan drying method. The objective of this study was to determine an appropriate temperature and drying time to produce high yield of antioxidant and antihypertensive activity. The materials used for this study were 900 eggs which were obtained from the same farm. That amount was calculated based on the number of experimental units required to run the experiment with the total number of treatment (3 x 3) with 4 replications for each treatment combination giving 25 chicken eggs for each treatment. The experiment was carried out using a 3x3 factorial arrangement according to completely randomized design. The first factor was drying temperature, i.e. 45oC, 50oC, and 55oC and the second factor was drying time, i.e. 30h, 39h, and 48h. The results showed that high antioxidant activity was found on egg white which was dried at temperature of 45oC for 39 hours which reached 26.85%. However, antihypertensive activity was optimum at 50oC and drying for 48 hours, which was up to 75.06%. Drying the egg white using appropriate temperature and time may improve the antioxidant and antihypertensive activities.